Sailor Twain : or, the mermaid in the Hudson - Siegel, Mark, 1967- (First Second, 2022)
"One hundred years ago. On the foggy Hudson River, a riverboat captain rescues an injured mermaid from the waters of the busiest port in the United States. A wildly popular--and notoriously reclusive--author makes a public debut. A French nobleman seeks a remedy for a curse. As three lives twine together and race to an unexpected collision, the mystery of the Mermaid of the Hudson deepens. A mysterious and beguiling love story with elements of Poe, Twain, Hemingway, and Greek mythology, drawn in moody black-and-white charcoal, this new edition of the New York Times Best-Selling graphic novel by author/illustrator Mark Siegel is a study in romance, atmosphere, and suspense. Don't miss Sailor Twain."--Amazon.com.